Recovery Of Oil From Palm Oil Mill Effluent (Pome) As Biodiesel Feedstock - Baharom, Amiranordiana (Universiti Sains Malaysia, 2022)
The global energy demand in the world has been increased tremendously, especially within developing countries. There are growing concern on the availability of fossils fuel that rapidly depleting as it keeps being used to produce energy to meet the demand. Therefore, greater attention has been placed on finding alternative renewable sources, such as biodiesel, which included producing fuel from oil made of plant or animal fat. Since Malaysia is one of the largest palm oil suppliers in the world, palm oil mill effluent (POME) has become a major source of pollution due to its high concentration of oil and grease content. Hence, this study is focusing on the recovery of oil from POME as a feedstock in the production of biodiesel. The oil is extracted using solvent extraction method, by varying types of solvent, solvent to POME ratio and extraction time to obtain the optimum condition for high yield of oil. N-hexane is the most suitable solvent with 2.6% of oil recovery for every 100 ml of POME at solvent to POME ratio of 1:1 and within 2 hours extraction time. Furthermore, the amount of biodiesel produced from 10 ml of oil extracted is about 8.67 g with most of the biodiesel characteristics in accordance with the biodiesel based on Malaysian standard MS 2800:2800.